Rāingān kānwičhai kānl̄ưaktang samāchik Saphā Phūth̄æn Rātsad̨ōn, 2 Karakadākhom 2538 (ʻĒkkasān singphim / K̨ōng Wichākān læ Ph̄ænngān, Krom Kānpokkhr̨ōng, 1996)
Study on general election, 1995 in Thailand, with objectives to find administrative orderliness and public participation.